2014
DOI: 10.1002/elps.201400013
|View full text |Cite
|
Sign up to set email alerts
|

Improving electrokinetic microdevice stability by controlling electrolysis bubbles

Abstract: The voltage-operating window for many electrokinetic microdevices is limited by electrolysis gas bubbles that destabilize microfluidic system causing noise and irreproducible responses above ∼3 V DC and less than ∼1 kHz AC at 3 Vpp. Surfactant additives, SDS and Triton X-100, and an integrated semipermeable SnakeSkin® membrane were employed to control and assess electrolysis bubbles from platinum electrodes in a 180 by 70 μm, 10 mm long microchannel. Stabilized current responses at 100 V DC were observed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 43 publications
(83 reference statements)
0
47
0
2
Order By: Relevance
“…[34][35][36] In addition to influencing bubble behavior, SLS can also be absorbed on the cathode surface. Gomez et al 37 found that SLS helped to render Zn electrodeposits more crystalline than other additives due to the larger overpotential evident in changes of voltammetry curves attributed to SLS adsorption.…”
Section: D844mentioning
confidence: 99%
“…[34][35][36] In addition to influencing bubble behavior, SLS can also be absorbed on the cathode surface. Gomez et al 37 found that SLS helped to render Zn electrodeposits more crystalline than other additives due to the larger overpotential evident in changes of voltammetry curves attributed to SLS adsorption.…”
Section: D844mentioning
confidence: 99%
“…This PBS microfluidic system previously demonstrated electrolysis bubble generation ; thus, electrode electrolysis reactions occur concurrent with carbon adsorption. During current measurements, electrolysis of water generates oxygen and hydrogen gas bubbles at the anode and cathode electrode surfaces, respectively .…”
Section: Resultsmentioning
confidence: 98%
“…Platinum wires were cut via scalpel and bent by tweezers to immerse 2 mm into each reservoir. General‐purpose epoxy (Henkel Corporation, Rocky Hill, CT, USA) attached platinum wire electrodes to a photolithographically fabricated PDMS microfluidic layer, as previously described .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(7) is satisfied by all DEP-FFF microdevices handling microparticles. Moreover, operation at high frequencies is advised in order to avoid corrosion of electrodes as well as gas generation at the interface between the electrode and the medium (Voldman, 2006); a recent work, Lee et al (2014), suggests addition of surfactants for mitigating gas generation in microfludic devices. Operation at high frequencies implies that the time period associated with the electric potential is extremely small thereby allowing for assuming it to be a constant, specifically the time averaged electric potential, i.e.…”
mentioning
confidence: 99%